The Influence of Applying the Picture and Picture (PAP) Learning Model on Student Learning Outcomes in Solar System Material - Sunaryo; Hermanto (Postgraduate, University of Mataram, 2024)
The research aims to examine the effect of implementing the Picture and Picture (PAP) Learning Model on Student Learning Outcomes in Class 6 Solar System Material at SDN 1 Socongkangsi. The research was carried out at SDN 1 Socongkangsi, class VI students. The sampling technique uses a purposive area sampling method. The research used a quasi-experimental design with data collection techniques through post-tests in the form of multiple choice questions and descriptions, observation, documentation and interviews. The data obtained was analyzed using statistical tests which included normality tests, data analysis using the Paired Samples t-Test. Based on the Validity Test, the results show r = 0.78 α >(0.05) so that all question items show valid results. Reliability test if the value α > 0.721 the value is reliable, namely 0.721. Then the results of the normality test, the learning outcome value is 0.386 > α (0.05) exceeds the significant value, then the variable value is normally distributed, followed by using the Paired Sample t-Test test, the test results -t is the learning result at a sig value of 0.00 < α (0.05), so reject H0. So it can be concluded that there is an influence of the application of the Picture and Picture (PAP) learning model on student learning outcomes in class 6 solar system material at SDN 1 Socongkangsi.